Clinical outcome of high dose rate brachytherapy with external beam radiotherapy for high-risk prostate cancer: a single institutional retrospective study. (23rd November 2018) - Shirotake, Suguru; Makino, Soichi; Suzuki, Kenjiro; Araki, Ryuichiro; Kosaka, Takeo; Nishimoto, Koshiro; Oyama, Masafumi; Kato, Shingo
Abstract : We retrospectively analyzed the clinical outcome of high dose rate brachytherapy for high-risk prostate cancer patients. Abstract: Objectives : This study investigated the clinical outcome of neoadjuvant androgen deprivation therapy followed by high dose rate brachytherapy (HDR-BT, called NEH) with external beam radiotherapy (EBRT) in high-risk prostate cancer (PCa) patients in our institution.Methods : From 2007 to 2012, 192 high-risk PCa patients underwent neoadjuvant treatment—EBRT—NEH ( n = 192). Relations between clinical factors (prostate-specific antigen; PSA, cT stage, Gleason score) and biochemical recurrence were retrospectively analyzed.Results : The 5- and 7-year overall survival rates were 97.9 and 91.1%. By PSA levels (PSA≤ 20 ng/ml, 20 ng/ml < PSA≤50 ng/ml and PSA > 50 ng/ml), 5-year biochemical recurrence-free survival rates were 85.7, 84.7 and 54.5%, respectively. There were no significant differences between biochemical recurrence and cT stage or Gleason score.Conclusions : We found that NEH can contribute to better biochemical recurrence free survival of high-risk PCa patients with PSA below 50 ng/ml. High-risk PCa patients with PSA over 50 ng/ml may require more aggressive local or systemic treatment.